THE USE OF PREDICT-EXPLAIN-OBSERVE-EXPLAIN IN IMPROVING THE STUDENTS’ SPEAKING ABILITY - Andi Asri Jumiati (Universitas Muhammadiyah Makassar, 2017)
This research aimed to explain the improved of the students’ accuracy and fluency in speaking. This research employed an Experimental design which was conducted in Pre-Test, Treatment, and Post-Test of five meetings. The location of this research was taken at eleventh year students of SMAN 1 Lilirilau Kabupaten Soppeng with a number of the subject were 35 students. The research findings indicate that the application of Predict-Explain-Observe-Explain was significant in improving the students’ accuracy and fluency in speaking. It was proved by the mean score of Pre-test was 3.48 then improved to be 8.32 in Post-test. And also there was significant because the result of t-test was 26.88 and t-table was 2.042. It mean that there was the improved of the students’ accuracy and fluency in speaking.